2021
DOI: 10.1097/qco.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Recent concepts in fungal involvement in skin and soft tissue infections

Abstract: As the at-risk population expands and new antifungal resistance patterns develop, it is critical to understand and recognize cutaneous manifestations of old and emerging fungal diseases. Purpose of reviewThe aim of this review is to provide an overview of the most frequent and emerging deep cutaneous fungal infections following either primary inoculation or secondary spread after haematogenous seeding in disseminated infections in different geographical areas. Recent findingsFungal skin and soft tissue infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Of note that poor glycemic control with high level of glycated hemoglobin (>7.5%) has been significantly associated with a 1.4-fold increased risk of cellulitis [10] Patients with cancer or history of cancer have an increased risk of RC, since surgery, radiotherapy and lymph nodes resection have lymphedema as a potential consequence. Of note that in cancer patients RC can occur in atypical sites and neutropenia may predispose to infections from atypical pathogens [11] Peripheral vascular disease, chronic kidney disease, chronic obstructive pulmonary disease, liver disease, homelessness and presence of foreign bodies are other risk factors for RC [2]…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note that poor glycemic control with high level of glycated hemoglobin (>7.5%) has been significantly associated with a 1.4-fold increased risk of cellulitis [10] Patients with cancer or history of cancer have an increased risk of RC, since surgery, radiotherapy and lymph nodes resection have lymphedema as a potential consequence. Of note that in cancer patients RC can occur in atypical sites and neutropenia may predispose to infections from atypical pathogens [11] Peripheral vascular disease, chronic kidney disease, chronic obstructive pulmonary disease, liver disease, homelessness and presence of foreign bodies are other risk factors for RC [2]…”
Section: Key Pointsmentioning
confidence: 99%
“…Patients with cancer or history of cancer have an increased risk of RC, since surgery, radiotherapy and lymph nodes resection have lymphedema as a potential consequence. Of note that in cancer patients RC can occur in atypical sites and neutropenia may predispose to infections from atypical pathogens [11]…”
Section: Risk Factors Associated With Recurrent Cellulitismentioning
confidence: 99%
“…Fungal SSTIs can be an important cause of morbidity and mortality in SOT patients and are being reported with increasing frequency worldwide [70 ▪▪ ]. Fungal SSTIs can be classified on the basis of their invasiveness in local superficial mycoses, subcutaneous mycoses and skin lesions in the context of disseminated fungal infection with multiorgan involvement [4,71,72].…”
Section: Fungimentioning
confidence: 99%
“…Superficial SSTIs with Candida spp. are the most frequent form of clinical presentation, whereas skin lesions are rare and usually associated with disseminated candidiasis [70 ▪▪ ].…”
Section: Fungimentioning
confidence: 99%
“…Studies have shown that the prevalence of superficial mycosis worldwide is as high as 20% to ~25%, indicating that fungi have partially replaced bacteria as the main pathogens ( 19 21 ). Untreated aggravation of deep SSTIs by Candida albicans can cause rapid necrosis of tissues and organs or spread into the blood, resulting in fungal septicemia and sepsis and even threatening the patient’s life ( 22 ). The situation of fungal infections is increasingly serious.…”
Section: Introductionmentioning
confidence: 99%